2004
DOI: 10.1093/jxb/erh178
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylsulphoniopropionate (DMSP) and related compounds in higher plants

Abstract: Dimethylsulphoniopropionate (DMSP) is produced in high concentrations in many marine algae, but in higher plants only in a few salt marsh grasses of the genus Spartina, in sugar canes (Saccharum spp.), and in the Pacific strand plant Wollastonia biflora (L.) DC. The high concentrations found in higher plants (up to 250 micromol g(-1) dry weight) suggest an important role, but though many functions have been suggested (including methylating agent, detoxification of excess sulphur, salt tolerance, and herbivore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 56 publications
1
83
0
Order By: Relevance
“…Previous investigators have focused on the production, function, and fate of DMSP in Spartina alterniflora (Pakulski & Kiene 1992, Otte & Morris 1994, Otte et al 2004, but none have shown that DMSP concentration affects Littoraria irrorata behavior as this study has. The ring assay showed that periwinkle snails are attracted to elevated levels of DMSP.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Previous investigators have focused on the production, function, and fate of DMSP in Spartina alterniflora (Pakulski & Kiene 1992, Otte & Morris 1994, Otte et al 2004, but none have shown that DMSP concentration affects Littoraria irrorata behavior as this study has. The ring assay showed that periwinkle snails are attracted to elevated levels of DMSP.…”
Section: Discussionmentioning
confidence: 80%
“…That DMSP may act as an L. irrorata attractant and not as a deterrent is further supported by the results of the ring assay. Twenty percent and 40% of L. irrorata were attracted to 10 µmol ml -1 and 90 µmol ml -1 DMSP, respectively, and no snails exhibited a negative behavior.Previous investigators have focused on the production, function, and fate of DMSP in Spartina alterniflora (Pakulski & Kiene 1992, Otte & Morris 1994, Otte et al 2004, but none have shown that DMSP concentration affects Littoraria irrorata behavior as this study has. The ring assay showed that periwinkle snails are attracted to elevated levels of DMSP.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Out of the 177 species of terrestrial angiosperms studied by Paquet et al (1995), only seven had a DMSP content per mass of dry weight (dw) between 0.1 and 1 mol g dw −1 , all the others being characterized by undetectable DMSP levels. Only a few species of higher plants have a high DMSP content, either strictly terrestrial plants such as sugar cane (Saccharum) and Wollastonia biflora and intertidal plants such as some species of Spartina (Otte et al, 2004;Dacey et al, 1987). The only study so far that has investigated the occurrence of DMSP in seagrasses was carried out by Dacey et al (1994) who attributed the occurrence of DMSP in samples from three species (Halodule wrightii, Syringodium filiforme, Thalas- * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Several physiological and ecological roles have been attributed to DMSP (Table 2). Some are common to phytoplankton, macroal- Table 1 Dimethylsulfoniopropionate (DMSP) content per dry wet (dw) (mol g dw −1 ) in major phytoplanktonic groups based on Stefels et al (2007), macroalgae based on Van Alstyne and Puglisi (2007), intertidal marsh plants based on Otte et al (2004) and Dacey et al (1987). The values for phytoplankton initially given in molS:molC were converted into dry weight using a carbon to total dry weight of 50% (Reynolds 2006).…”
Section: Introductionmentioning
confidence: 99%